Association of Increased Upper Trunk and Decreased Leg Fat With 2-h Glucose in Control and HIV-Infected Persons - Kosmiski, Lisa A. (American Diabetes Association, 2011)
OBJECTIVE: Changes in body fat distribution and abnormal glucose metabolism are common in HIV-infected patients. We hypothesized that HIV-infected participants would have a higher prevalence of impaired glucose tolerance (IGT) compared with control subjects. RESEARCH DESIGN AND METHODS: A total of 491 HIV-infected and 187 control participants from the second examination of the Study of Fat Redistribution and Metabolic Change in HIV Infection (FRAM) underwent glucose tolerance testing (GTT). Multivariable regression was used to identify factors associated with GTT parameters. RESULTS: The prevalence of impaired fasting glucose (IFG) (>110 mg/dL) was similar in HIV-infected and control participants (21 vs. 25%, P = 0.23). In those without IFG, the prevalence of IGT was slightly higher in HIV-infected participants compared with control subjects (13.1 vs. 8.2%, P = 0.14) and in HIV+ participants with lipoatrophy versus without (18.1 vs. 11.5%, P = 0.084). Diabetes detected by GTT was rare (HIV subjects 1.3% and control subjects 0%, P = 0.65). Mean 2-h glucose levels were 7.6 mg/dL higher in the HIV-infected participants (P = 0.012). Increased upper trunk subcutaneous adipose tissue (SAT) and decreased leg SAT were associated with 2-h glucose and IGT in both HIV-infected and control participants. Adjusting for adipose tissue reduced the estimated effects of HIV. Exercise, alcohol use, and current tenofovir use were associated with lower 2-h glucose levels in HIV-infected participants. CONCLUSIONS: In HIV infection, increased upper trunk SAT and decreased leg SAT are associated with higher 2-h glucose. These body fat characteristics may identify HIV-infected patients with normal fasting glucose but nonetheless at increased risk for diabetes.